Delphi consensus on gene therapy of spinal muscular atrophy with onasemnogene abeparvovec in Germany, Austria and Switzerland - part I - systematic literature review and existing evidence - Weiß, Claudia; Vill, Katharina; Baumann, Matthias; Bernert, Günther; Blaschek, Astrid; Eisenkölbl, Astrid; Flotats-Bastardas, Marina; Friese, Johannes; Ganter, Claudia; Goldhahn, Klaus; Hahn, Andreas; von der Hagen, Maja; et al. (Journal of neuromuscular diseases, 2025)
Background - Since the approval of onasemnogen abeparvovec (OA) for gene addition therapy in children with spinal muscular atrophy (SMA), there has been a considerable increase of evidence regarding its effectiveness and safety. Consequently, the previous recommendations needed to be revised. - Objective - The primary objective was to develop an evidence- and expert-based best practice protocol ensuring optimal patient safety and comprehensive support for affected families. The harmonization of treatment algorithms is expected to facilitate the collection of standardized real-world data, laying the foundation for future evidence-based adjustments. - Methods - A modified, two-part Delphi process was selected as a standardized methodology. Experts specializing in SMA from all 31 neuromuscular treatment centers within Germany, Austria and Switzerland, and patient advocacy groups participated in an industry-independent Delphi panel. Existing evidence concerning effectiveness, safety, and guidelines of OA was analyzed in a systematic literature followed by development of consensus statements regarding its effectiveness. - Results - Strong consensus was reached regarding the following statements on effectiveness: (1) OA gene addition therapy for SMA demonstrates a clear advantage compared to the natural progression of the disease. (2) Superiority of any of the three approved disease-modifying therapies has not been proven. (3) Earlier initiation of therapy with fewer symptoms and shorter disease duration leads to better outcomes. (4) There is no clinical evidence supporting the superiority of combining two treatments over monotherapy. - Conclusions: The systematic literature analysis constitutes the basis for the subsequent part 2, which involves the generation of expert-based recommendations for the surveillance of SMA gene addition therapy.
Vorab online veröffentlicht: 24. November 2025
Gesehen am 30.01.2026